Survival and Complication of Liver Transplantation in Infants: A Systematic Review and Meta-Analysis - Hou, Yifu; Wang, Xiaoxiao; Yang, Hongji; Zhong, Shan (Frontiers in Pediatrics, 2021)
Background: Modern surgical techniques and scientific advancements have made liver transplant (LT) in infants feasible. However, there are only a small number of studies examining the short as well as long term outcomes of LT in this vulnerable subset of children. Methods: Comprehensive searches were done systematically through PubMed, Scopus and Google scholar databases. Studies that were retrospective record based or adopted cohort approach and reported either patient survival rates or graft survival rates or complications of LT in infants were included in the meta-analysis. Statistical analysis was done using STATA version 13.0. Results: A total of 22 studies were included in the meta-analysis. The overall pooled patient survival rate at one year, >1 to 5 years and >5 years post-transplantation was 85% (95% CI: 78- 92%), 71% (95% CI: 59-83%) and 80% (95% CI: 69-91%) respectively. The overall pooled graft survival rate at one year, >1 to 5 years and >5 years post-transplantation was 72% (95% CI: 68- 76%), 62% (95% CI: 46-78%) and 71% (95% CI: 56-86%) respectively. The overall pooled rate for vascular complications, need for re-transplantation, biliary complications and infection/sepsis was 12% (95% CI: 10-15%), 16% (95% CI: 12-20%), 15% (95% CI: 9-21%) and 50% (95% CI: 38-61%) respectively. Conclusion: The current meta-analysis showed modest patient and graft survival rates for infant liver transplantation. However, the complication rates related to infection/sepsis were high. More comprehensive evidence is required from studies with larger sample sizes and a longer duration of follow-up.